SoTL tales: Lessons and reflections from the mathematics classroom - Chng, Huang Hoon; Tan, Victor; Bing, Yap Von (Teaching and Learning Inquiry, 2016)
A Review of Doing the Scholarship of Teaching and Learning in Mathematics edited by Jacqueline M. Dewar & Curtis D. Bennett.